Reutilization and upcycling of spent graphite for sustainable lithium-ion batteries: Progress and perspectives - Xueqian Li; Chenglong Deng; Mengyao Liu; Jiawei Xiong; Xiaodong Zhang; Qiaoyi Yan; Jiao Lin; Cen Chen; Feng Wu; Yi Zhao; Renjie Chen; Li Li (eScience)
In the development of sustainable lithium-ion batteries, achieving the efficient and cost-effective recycling of all components, particularly spent graphite (SG) anodes, has become a critical requirement. While considerable efforts have been devoted to recovering and reusing SG materials under conventional conditions, limited attention has been given to recycling under extreme conditions. This review systematically elucidates the main failure mechanisms of graphite anodes, including lithium plating and dendrite formation, solid electrolyte interface film failure, structural degradation, and current collector corrosion, with a particular focus on low-temperature and fast-charging conditions. As a contribution toward optimizing resource utilization, this review comprehensively summarizes the industrial perspective on strategies for recycling SG anodes, which aim to produce high-purity regenerated graphite (RG) powders. We also analyze current methods for modifying RG, such as structural reconstruction and surface reconditioning, to bring added value to modified RG materials. A detailed examination of the technical challenges in SG recycling and RG upgrading is presented, offering guidance for the future development of graphite upcycling technologies. This review also provides valuable insights into achieving high efficiency, intelligence, and sustainability in graphite utilization.